Indoor environmental risk factors for respiratory symptoms and asthma in young children. - Rumchev, Krassi (Curtin University, 2001)
Asthma is a common chronic disorder in Western countries and is increasing in prevalence in both children and adults. Although genetic risk for atopy is an important factor for the development of asthma, it does not explain the tremendous increase in prevalence seen in recent decades. Environmental exposures in early life that affect immune maturation appear to be the key factors for the development of asthma. The indoor environment is a likely candidate since infants spend 90% of the time indoors at a time when immune deviation usually occurs. Exposure to indoor pollutants represents a potentially modifiable cause of allergic sensitization and asthma. In this context, it becomes important to establish which environmental factors might influence the development of asthma in predisposed individuals. Allergic reactions to certain environmental allergens such as house dust mites, cats, and cockroaches, have shown a high level of association with asthma prevalence, but in the last five years increasing attention is being paid to indoor environmental factors, other than allergens, that may be involved in the development of this disorder. The potential irritants include nitrogen dioxide, environmental tobacco smoke, formaldehyde, volatile organic compounds, and particulate matter (PM[subscript]2.5;10).The aim of the study was to examine the nature of the relationship between asthma and environmental exposure to indoor environmental irritants.A population based case-control study had been carried out in Perth, Western Australia. The study population consisted of young children (N = 192) aged between 6 months and 3 years old. Cases (n = 88) were asthmatic children who attended the Accident and Emergency Department at Princess Margaret Hospital for Children and were discharged with asthma as a primary diagnosis. Controls (n = 104) were children in the same age group as cases who had never been diagnosed with asthma, identified from birth records accessed through the Health Department of Western Australia. Information, regarding the respiratory conditions experienced by the study children and characteristics of the home, was collected using a standardised questionnaire. The questionnaire consists of questions about potential risk factors for asthma and these factors were grouped in three categories. The first category included information on personal and social factors such as age and gender of the child, and mother's and father's educational level. The second category was related to personal susceptibility factors such as child's allergy, parental and sibling's asthma, eczema and hay fever. The last category included environmental exposure in the house such as parental and visitors smoking inside the house, exposure to gas heating and cooking, kerosene space heaters, open fireplaces, and pets. Other questions related to environmental exposure were the presence of air conditioning, humidifiers, and type of floor covering in the child's bedroom and the living room. Measurements of indoor nitrogen dioxide (NO[subscript]2), formaldehyde (HCHO), volatile organic compounds (VOCs), particulate matter (PM[subscript]10), and house dust mite exposure were made on two occasions over one year, winter (middle June through September 1998) and summer (December 1998 through March 1999), Indoor temperature and relative humidity were also measured. The atopic status of the children was assessed by skin prick tests to common allergens.The study results indicated that age, gender, family history of asthma, atopy and domestic exposure to indoor environmental factors were significant predictors of asthma early in life. The study found that indoor exposure to formaldehyde, volatile organic compounds and house dust mite significantly increased the risk of having asthma. Presence of air conditioning appeared to be a protective factor for asthma.In conclusion, the study results confirmed the role of susceptibility factors in asthma and show that indoor environmental factors contribute as risk factors for asthma in early stage of fife. The observation that exposure to indoor air pollutants in early childhood is associated with asthma suggests the possibility that irritants in indoor air might be involved in the initiation phase of asthma. Since the quality of the indoor environment is potentially modifiable there might be opportunities for intervention to reduce asthma symptoms. In order to counteract the increasing prevalence in asthma, the significance of the indoor environment where children grow and spend most of their time need to be given greater attention.